SOMATOTYPE DISTRIBUTION IN STUDENTS OF SPORTS ACADEMY AND MEDICAL SCHOOL - Ayhan Kamanlı,; Recep Özmerdivenli,; Kürşat Karacabey,; Mehmet Kutlu,; Özge Ardıçoğlu, (Archives of Rheumatology, 2003)
Objective: The purpose of this study was to investigate the difference in somatotype, % fat, body mass index (BMI) between Sports Academy students (SAS) who were actively engaged in sports and Medical School students (MSS) Design and Material: Sixty (30 male, 30 female) Sports Academy students and twenty four (14 male, 10 female) Medical School students participated in this study as volunteers. Body composition was estimated from skinfold and somatotype was determined using the Heath-Carter method. Data analysis included antropometric measures and three somatotype variables (endomorphy, mesomorphy, ectomorphy), were compared between groups and sexes, and the level of significance was set at 0.05. Results: Thorax, abdominal and hip circumference of sports academy students were significantly higher (p<0.05). Suprailiac, abdominal, upper arm triceps and subscapular skinfold of medical school students were found significantly higher (p<0.01). Between the groups the mean mesomorphic (SAS: 2,42±1,24 and MSS: 2,29±1,24) and ectomorphic components (SAS: 3,01±0,93 and MSS: 2,79±1,02) and diameter of bicondylar of femur and humerus were not significantly different (p>0.05). The endomorphic component was found significantly different (SAS: 2,15±0,75, MSS: 2,69±0,74) (p<0.05). The amount of endo-ectomorphs were higher in both groups. SAS were mainly classified as endo-ectomorph, meso-ectomorph and ekto-mesomorph. The average values of mesomorphy and endomorphy were found different from sex point of view (p<0.001). In both groups, mean percent body fat and endomorphy was found significantly higher (p<0.05, p<0.001 respectively) in the females. Conclusion: The amount of endomorphy and % fat was higher in the MSS group than SAS group. The endomorphic component of females was found higher than males in both groups. The endo-ectomorphic, meso-ectomorphic and ekto-mesomorphic somatotypes were significantly higher in SAS. It may be concluded that amount of endomorphic component of active people decreases significantly.